Diverse Swards and Mixed-Grazing of Cattle and Sheep for Improved Productivity - Jerrentrup, Jana Sabrina; Komainda, Martin; Seither, Melanie; Cuchillo-Hilario, Mario; Wrage-Mönnig, Nicole; Isselstein, Johannes (Frontiers in Sustainable Food Systems, 2020)
Increasing sward phytodiversity has been suggested as having potential to increase primary production of grasslands, but whether any such gains are converted into secondary production, through improved performance of grazing livestock, remains uncertain. Animal production by cattle and sheep can also be enhanced by mixed-grazing. To our knowledge, this effect has never been studied in relation to differences in sward phytodiversity. Therefore, a rotational grazing experiment was conducted over 5 years (2007–2011) on permanent grassland in Germany using sheep and cattle in mono- (single-species) or mixed-grazing of swards differing in plant species richness. Herbicides against dicotyledonous plant species were used to create different sward types: species-poor, grass-dominated swards in contrast to untreated “diverse” control swards. We found no differences in herbage production between the sward types. However, compared to the grass-dominated sward, the diverse sward showed greater concentrations of crude protein and lower contents of acid detergent fiber in the herbage dry-matter. Lamb live weight gains were slightly greater on the diverse-swards (P < 0.05), but calf performance was unaffected by sward type. Mixed-grazing increased daily average live weight gains of suckler cows (g cow−1 d−1) (P < 0.05) as well as area-related daily live weight gains (kg ha−1 d−1) and total live weight gains (kg ha−1) during the complete grazing season (P < 0.001). This indicates advantages of combining livestock species, attributed to complementary pasture use. We suggest that mixed-grazing of cattle and sheep on phytodiverse swards is an effective and sustainable means to enhance ecological and agronomic traits such as livestock production and plant species conservation. Lamb production especially showed benefits under mixed-grazing, with a 17% increase in live weight gain. Compared to the grass-dominated sward, diverse swards resulted in an average 12% increase of live weight gains (across grazing systems and livestock species).